2015
DOI: 10.1007/s11041-015-9877-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Treatment on Mechanical Properties and Phase Composition of Magnesium-Aluminum Composite Prepared by Explosive Welding

Abstract: Results are given for a study of the effect of heat treatment regimes on the nature of change in micromechanical properties and phase composition of magnesium-aluminum composite material AD1-MA2-1 prepared by explosive welding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…After explosive welding, ultrasonic examination (US) was employed to inspect the bonding interface of clad plates with OLYMPUS 5077 equipment [5]. Then, the samples were cut parallel to the detonation direction.…”
Section: Specimen Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…After explosive welding, ultrasonic examination (US) was employed to inspect the bonding interface of clad plates with OLYMPUS 5077 equipment [5]. Then, the samples were cut parallel to the detonation direction.…”
Section: Specimen Characterizationmentioning
confidence: 99%
“…Explosive welding is noted for its capability of offering high strength bonding and cladding metals that are unweldable or are difficult to weld by other methods. It has been developed as a promising way to clad dissimilar materials [5][6][7][8][9][10][11][12][13]. Thus, some attempts have been made to clad other materials on Mg alloys by explosive welding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the existence of intermetallic compounds was not observed, but the presence of a solid solution with a chemical composition changing in the direction from the weld to the base materials was found. The authors [19][20][21][22] studied the effect of annealing on the formation of intermetallic phases in the structure of Al/Mg composites produced by the EXW method. They found that heat-treatment leads to the development of the intermetallic phases: β-Mg2Al3 and γ-Mg17Al12.…”
Section: Introductionmentioning
confidence: 99%